Laparoscopic Repair of Cholecysto-enteric Fistula: Report of Two Cases (Bangladesh Journal of Endosurgery, 2014)
Laparoscopic procedure is the gold standard for gallstone diseases. Cholecystoenteric  fistula is a rare complication of gallstone diseases and mostly diagnosed  during laparoscopic cholecystectomy or open procedure. These conditions can  also be treated by laparoscopic method. Out of 4 cases, 2 have been treated by  laparoscopic procedure. One is cholecysto-gastric fistula and other is cholecystoduodenal  fistula. To close and dissect the tract the authors used suture and plastic  clip instead of linear transecting stapler device to cut down cost and minimize the  port size without compromising safety.DOI: http://dx.doi.org/10.11593/bje.2013.0103.0018Bangladesh Journal of Endosurgery Vol.1(3) September 2013: 6-8